Peptide Agonists of Vasopressin V2 Receptor Reduce Expression of Neuroendocrine Markers and Tumor Growth in Human Lung and Prostate Tumor Cells - Pifano, Marina; Garona, Juan; Capobianco, Carla S.; Gonzalez, Nazareno; Alonso, Daniel F.; Ripoll, Giselle V. (Frontiers in Oncology, 2017)
Neuroendocrine tumors (NETs) comprise a heterogeneous group of malignancies that express neuropeptides as synaptophysin, chromogranin A and NSE, among others. Vasopressin (AVP) is a neuropeptide with an endocrine, paracrine and autocrine effect in normal and pathological tissues. AVP receptors are present in human lung, breast, pancreatic, colorectal and gastrointestinal tumors. While AVP V1 receptors are associated with stimulation of cellular proliferation, AVP V2 receptor (V2r) is related to antiproliferative effects. dDAVP is a synthetic analog of AVP that acts as a selective agonist for the V2r, which shows antitumor properties in breast and colorectal cancer models. Recently, we developed a derivative of dDAVP named [V4Q5]dDAVP, which presents higher antitumor effects in a breast cancer model compared to the parental compound. The goal of present work was to explore the antitumor properties of the V2r agonist dDAVP and its novel analog [V4Q5]dDAVP on aggressive human lung (NCI-H82) and prostate cancer (PC-3) cell lines with neuroendocrine (NE) characteristics. We study the presence of specific NE markers (CgA and NSE) and V2r expression in NCI-H82 and PC-3. Both cell lines express high levels of NE markers NSE and CgA but then incubation with dDAVP diminished expression levels of both markers. DDAVP and [V4Q5]dDAVP significantly reduced proliferation, doubling time and migration in both tumor cell cultures. [V4Q5]dDAVP analog showed a higher cytostatic effect than dDAVP, on cellular proliferation in the NCI-H82 cell line. Silencing of V2r using siRNA significantly attenuated the inhibitory effects of [V4Q5]dDAVP on NCI-H82 cell proliferation. We preliminary explored the in vivo effect of dDAVP and [V4Q5]dDAVP on NCI-H82 SCLC xenografts. Treated tumors (0.3 ugkg-1 thrice a week) grew slower rate in comparison to vehicle-treated animals. In this work we demonstrated that the specific agonists of V2r, dDAVP and [V4Q5]dDAVP displays antitumor capacity on different human models of lung and prostate cancers with NE features, showing their potential therapeutic benefits in the treatment of these aggressive tumors.